Efforts to Unravel the Complexity of Election and Election Crimes in Indonesia - Hanum, Cholida (Law Research Review Quarterly, 2018)
Problems in electoral law are more complex than those in other legal regimes. The many types of problems and the large number of institutions involved in handling elections and general elections indicate the complexity of electoral law and election problems. There are six types of problems in election and general election law, namely violations of the code of ethics for election and general election organizers, electoral and electoral disputes, administrative and electoral violations, election and general election crimes, election results disputes and administrative disputes election and general election countries. Whereas various institutions involved in the election and general election law include the General Election Commission (KPU), Election Supervisory Body and general election (Bawaslu), Honorary Election and Election Organizing Board (DKPP), Indonesian Police, District Courts and High Courts, Courts State Administration and State Administrative High Court, Supreme Court, Constitutional Court and Indonesian Broadcasting Commission. The complexity of the electoral law and general elections is inherent in the realm of election and general election crimes. The regulation and law enforcement of election and general election are a separate problem, especially in terms of the mechanism for resolving election and general election crimes. Recently the Supreme Court has issued Regulations relating to the settlement of election and general election crimes. This study will examine the mechanism for resolving criminal acts in elections and general elections in the Supreme Court Regulation No. 1 of 2018 concerning the settlement of election crimes and general elections related to the politics of criminal law in Indonesia.